Perhitungan Nilai Besaran Fisis Mammografi Jenis Histopatologi IDC dan ILC - Frady Cakranegara, Anak Agung Ngurah; Putra, Ida Ayu Gde Suwiprabayanti (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023DO - 10.24843/JNATIA.2023.v01.i03.p17, 2023)
In this study, the main objective was to calculate the range of physical values contained in mammography X-ray images and determine the physical quantities that are significant in differentiating between the histopathological types of ILC (Invasive Lobular Carcinoma) and IDC (Invasive Ductal Carcinoma). The research method involved collecting data from 152 mammograms consisting of 7 ILCs and 145 IDCs from doctor Sutomo Surabaya's radiology database. The range of physical values such as entropy, contrast, second angular moment, differential invest moment, mean, deviation, entropy of Hdiff, angular moment of Hdiff, and mean of Hdiff are calculated and compared between ILC and IDC using the Anova statistical test. The results showed that there were differences in the range of physical quantity values between ILC and IDC. Significant parameters in differentiating the two types of histopathology are mean1, mean2, mean3, and mean4. In conclusion, IDC has a higher peak than ILC, and the range of ILC physical quantities is higher than IDC.